Status of hepatitis B virus in the aetiology of uveitis in Great Britain. Issue 10 (October 1983) - Murray, P I; Prasad, J; Rahi, A H
Abstract : Viruses have been demonstrated or suspected as the causative agents of various types of uveitis. Hepatitis B virus (HBV), apart from causing hepatitis, has also been implicated in the pathogenesis of systemic vasculitis, for example in glomerulonephritis and polyarteritis nodosa. It is therefore possible to postulate that a similar vasculitic process might occur in the eye leading to intraocular inflammation. A recent report from Switzerland suggests that HBV may be implicated in the aetiology of uveitis, as hepatitis B surface antigen (HBsAg) was found in the serum of 13% of cases of uveitis. Since the status of HBV in the aetiology of uveitis in Great Britain has not been investigated, we have examined serum from 200 cases of uveitis of various clinical types for the presence of circulating HBsAg. Only 4 cases (2%) were found to be HBsAg positive. This study failed, therefore, to confirm HBV as an important cause of uveitis in this country, but one cannot exclude the possibility that it may play a pathogenetic role in a small proportion of such cases.